Photovoltaic Performance of Porphyrin‐Based Dye‐Sensitized Solar Cells with Binary Ionic Liquid Electrolytes. Issue 6 (24th April 2020) - Bahadar Khan, Sher; Yadav, Pankaj Kumar; Decoppet, Jean-David; Yi, Chenyi; Al-Ghamdi, Mohammed S. A.; Alhogbi, Basma G.; Asiri, Abdullah M.; Zakeeruddin, Shaik M.; Grätzel, Michael
Abstract : Herein, green porphyrin sensitizer Y350‐based dye‐sensitized solar cells (DSCs) with binary ionic liquid–based electrolytes are studied, which are a mixture of 1‐methyl‐3‐propyl‐imidazolium iodide and 1‐methyl‐1‐butylpyrrolidinium bis(trifluromethylsulfonyl) ‐imide, 1‐butylpyridinium bis(trifluromethylsulfonyl)imide, 1‐methyl‐3‐ethylimidazolium bis(trifluromethylsulfonyl)imide, or 1‐methyl‐3‐ethylimidazolium tetracyanoborate. The best semitransparent green DSC device exhibits a short‐circuit photocurrent density of 9.1 mA cm −2, an open‐circuit photovoltage of 727 mV, and a fill factor of 70%, corresponding to an overall power conversion efficiency (PCE) of 4.9% under standard AM 1.5G illuminations at 100 mW cm −2 . The PCE increases to 6.1% with opaque films containing larger light‐scattering TiO2 particles. Abstract : Green porphyrin dye Y350‐based dye‐sensitized solar cells (DSCs) with low‐viscosity binary ionic liquid electrolytes achieve over 6% power conversion efficiency under standard AM 1.5G illuminations at 100 mW cm −2 .